Female students' participation (over the years) in esports and its implications on psychological conditions, communication, and virtual gaming risks - Berliana Berliana; Nina Sutresna; Ivan Rivan Firdaus; Dandi Elfanni; Yuski Ardiyansi; Jusuf Blegur; Ayuning Maharesti (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
eSport is a sport of choice and is quite popular, especially among young people, including women. This virtual sport has been developed entirely with various ways to play. At the same time, there is a negative paradigm of eSport games for women in Indonesia, including damaging vision, causing numbness in the hands, forgetting to eat, being introverted, and using harsh language. From a cultural perspective, women who play eSport are considered to violate the nature of women because they reflect masculine characteristics. This study uses quantitative research with a causal-comparative design to examine the effect of female students' participation in playing eSports on psychological development, communication skills, and the risks of virtual games. The research data were analyzed descriptively and inferentially (Multivariate Analysis of Variance). The analysis results prove a simultaneous influence between eSport participation (duration of playing) and ​​female students' psychological conditions, communication, and virtual game risks. In partial testing, eSport participation only significantly affected the communication skills variable of female students, while the other two variables did not. Future research needs to conduct qualitative investigations to explore the clinical experiences of female gamers that help them train their communication skills. Given the existence of various gender discriminatory behaviours in eSports, female gamers may have good communication to protect themselves from the threat of discrimination, or vice versa.